(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
The article seeks to foster reflection on the international order. The article aims to examine the impact in international monetary system under the dominance of the dollar as key currency and the possibility of forming a basket of currencies between countries in order to have a more balanced international.